Apoptosis and asthma in the elderly - Todo-Bom, A. (2007)
Background: Asthma is a chronic inflammatory disorder of the airways. The persistence of airway inflammation depends on a decrease in apoptosis of T lymphocytes and eosinophils and survival of these activated cells. T lymphocytes expressing gamma delta receptors can be identified in human lungs and play an important role in immune defence against pathogens and in the regulation of chronic inflammation. Aging is associated with evidence of some immune dysregulation. Objective: The aim of this study was to analyze the apoptosis receptors of T lymphocytes in long-lasting asthma, to establish their correlation with activation markers such as CD25+ and human leukocyte antigen (HLA)-DR+, and to analyze the gama delta T cell expression in this disease. Methods: A group of 64 individuals (group A) who had had asthma for more than 30 years (mean age [+/-SD] 72 +/- 5 years) and 61 healthy individuals acting as controls--group B with 41 individuals (mean age 79 +/- 7 years) and group C with 20 individuals (mean age 38 +/- 12 years) were included in the study. All subjects underwent clinical evaluation and spirometric testing. Peripheral blood cells were stained with monoclonal antibodies anti-CD3, anti-CD4, anti-CD8, anti-CD25, anti-TCR gamma delta, anti-HLA-DR and anti-CD95. Statistical comparisons were performed between the asthmatics and the elderly control group and between the elderly control group and the adult control group. Results: The average percentage of predicted forced expiratory volume in the first second was 73.6 gamma delta 25.3. The mean values of T cell receptors for asthma group A vs elderly control group B vs adult control group C respectively, were the following: CD3, 74.9+/-7 vs. 74.8 +/- 8.8 (P=ns) vs. 76.7 +/- 4.2 (P=ns); CD4, 48.8 +/- 8.7 vs. 43.5 +/- 10.2 (P=ns) vs. 44.8 +/- 3.8 (P=ns); CD8, 23.3 +/- 7.9 vs. 25.7 +/- 10.2 (P=ns) vs. 25.6 +/- 4.5 (P=ns); CD25, 14.3 +/- 5.9 vs. 22.4 +/- 7.8 (P = .0001) vs. 5.5 +/- 2.4 (P = .0001); TCR gamma delta, 2.8 +/- 2.1 vs. 4.1 +/- 3.3 (P < .05) vs. 4.6 +/- 2.1 (P=ns); HLA-DR, 18.4 +/- 9.2 vs. 17.8 +/- 5.9 (P=ns) vs. 15.4 +/- 5.1 (P=ns) and CD95, 49.3 +/- 13.7 vs. 52.6 +/- 12.1 (P=ns) vs. 13.8 +/- 10.8 (P = .0001). Conclusions: The immunological and inflammatory changes related to ageing may cause an increase in CD95 and CD25 T cell expression. In asthma, blood cells may express increased activation and apoptosis markers but in elderly patients taking steroids, these receptors remain within normal ranges. The number of gamma delta T cells may be lower in long-lasting asthma, and have a limited modulatory effect on allergic inflammatory reactions. The evaluation of patients with long-lasting asthma should take into account the immunological and inflammatory changes present in the elderly in order to avoid results being misinterpreted.